Preparation and characterization of a titanium alloy with the addition of tantalum and zirconium for biomedical applications - Kuroda, Pedro Akira Bazaglia [UNESP]; Do Nascimento, Mycaella Vieira; Grandini, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2020)
Titanium alloys are widely used in the biomedical field due to its excellent corrosion resistance in bodily fluids, high mechanical strength/density ratio, low elastic modulus and good biocompatibility. The most promising alloys to be used in the biomedical field have solid solution elements that decrease the phase trans-formation temperature of titanium. Such elements are called beta-stabilizers and are obtained as a result of their introduction in the alloy, the decrease of the elastic modulus and an excellent corrosion resistance. Tan-talum and zirconium elements, when added to the titanium, improve the corrosion resistance and diminish the elastic modulus, because tantalum is considered a β-stabilizer element and the zirconium acts as a stabilizing element of this phase, in presence of another β-stabilizer element. In this paper, Ti-25Ta-5Zr alloy was pre-pared by arc-melting, aiming biomedical applications. The chemical, structural, microstructural and mechanical characterizations were performed by means of chemical composition measurements, gas analysis, energy dispersive spectrometry (EDS), X-ray diffraction, optical and scanning electron microscopies, Vickers mi-crohardness and elastic modulus. The obtained results showed a good stoichiometry and homogeneity of the samples. Structural and microstructural analyses corroborated each other and indicated that the alloy has the coexistence of two phases, α (with orthorhombic crystalline structure) and β (with body-centered cubic structure). The microhardness increased with the addition of such elements and the elastic modulus has val-ues below the commercially used alloys, satisfactory for application as orthopedic implant.
Preparação e caracterização de uma liga de titânio com a adição de tântalo e zircônio para aplicações biomédicas
Keywords: Biomaterials; Microstructure; Titanium alloys